Singapore-ONE network characterization and performance analysis - Annam Vaidhiyanathan (2008)
This thesis provides a documentation of the design, development and simulation of the Singapore-ONE network model and the analysis of the results obtained. Singapore-ONE is a nation-wide ATM installation that will provide broadband services to every business, school, home and office. This is the first ATM installation in the world, which integrates both the telephone and cable infrastructure. The S-ONE network consists of 8 ATM switches. ATM is a new technology and Singapore-ONE is first of its kind in Singapore. So it is essential to study its performance to optimize the quality of service it provides to the users.